2013
DOI: 10.1155/2013/362750
|View full text |Cite
|
Sign up to set email alerts
|

Oral Lichen Planus in Thai Patients Has a Low Prevalence of Human Papillomavirus

Abstract: Background. Oral lichen planus (OLP) is a common chronic inflammatory immune-mediated disease, with an etiopathogenesis associated with cell-mediated immunological dysfunction. Viral infection has been hypothesized as a predisposing factor in the pathogenesis of this disease. Viruses may alter host cell function by inducing the abnormal expression of cellular proteins leading to disease development. However, reports on the relationship between human papillomavirus (HPV) and OLP are inconclusive. Objective. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…The main information of the 22 selected studies is listed in Table 1 . The analysis covered 12 countries, 5 of Asia, specifically China [ 16 – 20 ], India [ 9 , 10 ], Iran [ 21 ], Thailand [ 22 ], and Turkey [ 23 ]; 6 in Europe, specifically Italy [ 12 , 13 , 24 , 25 ], Hungary [ 26 , 27 ], England [ 5 , 11 ], Germany [ 8 ], Ireland [ 28 ], and Sweden [ 29 ]; 1 in North American, specifically the United States [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…The main information of the 22 selected studies is listed in Table 1 . The analysis covered 12 countries, 5 of Asia, specifically China [ 16 – 20 ], India [ 9 , 10 ], Iran [ 21 ], Thailand [ 22 ], and Turkey [ 23 ]; 6 in Europe, specifically Italy [ 12 , 13 , 24 , 25 ], Hungary [ 26 , 27 ], England [ 5 , 11 ], Germany [ 8 ], Ireland [ 28 ], and Sweden [ 29 ]; 1 in North American, specifically the United States [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, HPV-DNA has been observed in a small proportion (6.4%) of dysplasias in preliminary results of a recent Canadian study [20]. Regarding OLP, a low HPV-DNA prevalence was reported in thirty-seven fresh-frozen tissue biopsy specimens from OLP lesions tested for HPV-DNA where only one sample was positive [34]. Other studies [35,36] also showed very low prevalence in OLP and premalignant conditions.…”
Section: Discussionmentioning
confidence: 96%
“…It has been reported in many studies that the most common type of HPV infection in OLP is HPV-16 infection 11,20,24,35,36) .…”
Section: Discussionmentioning
confidence: 99%